Money in motion: Dynamic portfolio choice in retirement - Wolfram J. Horneff; Raimond H. Maurer; Olivia S. Mitchell; Michael Z. Stamos (Goethe University Frankfurt, Center for Financial Studies (CFS), 2007)
Retirees confront the difficult problem of how to manage their money in retirement so as to not outlive their funds while continuing to invest in capital markets. We posit a dynamic utility maximizer who makes both asset location and allocation decisions when managing her retirement financial wealth and annuities, and we prove that she can benefit from both the equity premium and longevity insurance in her retirement portfolio. Even without bequests, she will not fully annuitize; rather, her optimal stock allocation amounts initially to more than half of her financial wealth and declines with age. Welfare gains from this strategy can amount to 40 percent of financial wealth (depending on risk parameters and other resources). In practice, it turns out that many retirees will do almost as well by purchasing a variable annuity invested 60/40 in stocks/bonds.
urn:nbn:de:hebis:30-44551
Keywords: G11; G23; G22; D14; J26; H55; 330; Portfolio Choice; Private Financial Services; Insurance; Personal Finance; Retirement Policies; Social Security; Alterssicherung; Portfolio-Management; Wertpapieranlage; Aktie; Dynamische Investitionsrechnung